Working outside 'the rules': Opportunities and challenges of community participation in risk reduction. (April 2020) - Haynes, Katharine; Bird, Deanne K.; Whittaker, Joshua
Abstract: Research has shown that greater community action is needed for effective risk reduction. Community participation in risk reduction ranges from action that is initiated and led by members of the public, independently of government assistance, to those that are initiated and facilitated by government and non-government organisations. Natural hazards research has demonstrated that despite awareness of and a desire to reduce risk, many community members lack the physical, psychological or financial capacity to take action. This is particularly the case for bushfires, where preparations can be costly and physically demanding. In response to this, Fire and Rescue New South Wales (FRNSW) established the Community Fire Unit (CFU) program. CFUs are groups of residents who are provided with education, training and equipment to enable them to reduce risks around their homes through enhanced preparation and some bushfire defence. This paper examines the experiences and views of CFU members after bushfires in the Blue Mountains, NSW in October 2013. The majority of respondents believed that their participation in the CFU program reduced bushfire risk and led to a greater sense of community and social capital in their local area. However, the research revealed challenges associated with participating within the formal, top-down structures of a professional fire brigade. Respondents therefore considered that greater flexibility was needed with simultaneously greater support and autonomy from FRNSW. The paper explores the experiences, challenges and opportunities presented by a top-down community based risk reduction program and considers the implications for community participation in risk reduction more generally.